Myeloid-Derived Suppressor Cells in Kidney Transplant Recipients and the Effect of Maintenance Immunotherapy - Iglesias-Escudero, María; Sansegundo-Arribas, David; Riquelme, Paloma; Merino-Fernández, David; Guiral-Foz, Sandra; Pérez, Carmen; Valero, Rosalia; Ruiz, Juan Carlos; Rodrigo, Emilio; Lamadrid-Perojo, Patricia; Hutchinson, James A.; Ochando, Jordi; et al. (Frontiers in Immunology, 2020)
Myeloid Derived Suppressor Cells (MDSC) represent a heterogeneous group of myeloid regulatory cells that were originally described in cancer. Several studies in animal models point to MDSC as important players in the induction of allograft tolerance due to their immune modulatory function. Most of the published studies have been performed in animal models and the data addressing MDSCs in human organ transplantation is scarce. We evaluated the phenotype and function of different MDSCs subsets in 38 kidney transplant recipients (KTR) at different time-points. Our data indicates that monocytic-MDSCs (Mo-MDSC) increase in KTR at 6 months and 12 months post-transplantation. On the contrary, the percentages of polymorphonuclear MDSC (PMN-MDSC) and early stage MDSC (e-MDSC) are not significantly increased. We evaluated the immunosuppressive activity of Mo-MDSC in KTR and confirmed their ability to increase regulatory T cells (Treg) in vitro. Interestingly, when we compared the ability of Mo-MDSC to suppress T cell proliferation we observed that tacrolimus, but not rapamycin treated KTR, was able to inhibit CD4+ T cell proliferation in vitro. This indicates that, although mTOR inhibitors are widely regarded as supportive of regulatory responses, rapamycin may impair Mo-MDSC function and suggests that the choice of immunosuppressive therapy may determine the tolerogenic pathway and participating immune cells that promote organ transplant acceptance in KTR.